Native foods from Peru to the world - Blanco de Alvarado-Ortiz, Teresa (2016)
I am writing my 12th book in my aim to contribute to Universidad San Ignacio de Loyola’s commitment to cast a spotlight on the importance of Peru’s indigenous foods, popular for their nutrition and health properties, flavor, aroma, different colors and rich phytochemical content, the foundation of a cuisine that is highly valued today across the globe. Also worth recognizing is the fact that, in our country, vegetable production is a determinant of our national heritage.